Modelling of a continuous veneer drying unit of industrial scale and model-based ANOVA of the energy efficiency. (1st April 2022) - Gradov, Dmitry Vladimirovich; Yusuf, Yusuf Oluwatoki; Ohjainen, Jussi; Suuronen, Jarkko; Eskola, Roope; Roininen, Lassi; Koiranen, Tuomas
Abstract: Drying, a crucial step in process engineering aimed at producing optimal product moisture content, has evolved over time from batch processing methods to continuous processing alternatives. Continuous drying methods offer uniform moisture content of the product at lower operational cost. In this study, a continuous veneer drying model was developed based on mass and energy balances. The simulated veneer dryer is a semiautomatic machine designed to maximise the drying process efficiency via control mechanisms such as the veneer transport rate, fan speed, opening angle of the inlet and outlet dampers, and radiator temperature. In the dryer, veneer plates are conveyed horizontally through the number of connected chambers where hot air is blown transversely. The optimal drying process is dynamically maintained via the Proportional–integral–derivative controllers, manipulating the rate of the damper lids opening, that are connected to the sensors monitoring the air properties in the chambers of the drying unit. The model-based sensitivity analysis ANOVA was carried out for energy optimisation purposes. The analysis outcomes indicated that radiator temperature, initial moisture content of veneer sheets and conveyor speed are the most influential parameters affecting the drying rate. Automatic control of damper lids provides optimal temperature and moisture content of drying environment at lower energy costs. Highlights: A comprehensive numerical model of convective drying in an industrial veneer dryer is presented. An automated control system for inlet and exhaust lids targets the atmosphere optimal for the drying. Dynamic regulation of the lids showed best energy efficiency preventing overdrying of veneers. The model-based ANOVA was carried out for energy optimisation purposes.